Filantropi Dalam Islam Dan Implikasinya Terhadap Kondisi Sosial-Ekonomi Masyarakat (Perspektif Hukum Ekonomi Syariah) - Mariani; Rezki Mawaddah (CV. Kalimasada Group, 2025)
Islamic philanthrophy through zakat, infaq, sadaqah and waqf plays a strategic role in fostering social justice and economic welfare within society. However, the implementation of Islamic philantrophy often faces chalengges due to suboptimal magament, low public literacy, and various other factor. This study aims to analyze the practices of islamic philanthropy and their implication for the socio-economic conditions of society, as well as evaluate the role of sharia economic law regulations in supporting the succes of these practices. Based on this, the author seeks to understand the concpet of Islamic philanthrophy and how its practices impact the socio-economic conditions of society from the perspectiveof sharia economic law. This research employs normative methods with a conceptual approach and descriptive-qualitative data analysis. The findings indicate that Islamic philanthropic practices have significantly impacted society’s sosio-economic conditions, though their potential remains underutilized. The presence of Islamic philanthrophy contributes to poverty alleviation and reduces socio-economic disparities when managed effectively and optimized. Its benefits can be maximized through good governance and supported by various regulations that facilitate and regulates its implementation.